Electrical discharge grinding versus abrasive grinding in polycrystalline diamond machining—tool quality and performance analysis. Issue 1 (July 2016) - Rahim, Mohammad; Li, Guangxian; Ding, Songlin; Mo, John; Brandt, Milan
Abstract Electrical discharge grinding (EDG) and conventional abrasive grinding are two different methods to machine polycrystalline diamond (PCD) with different removal mechanisms. This paper discussed the quality issues of PCD tools produced by the two processes. Although remarkably similar surface roughness and tool sharpness were obtained in both processes, it was found that residual stress and the level of graphitization were significantly different. In this study, residual stress and graphitization were analyzed quantitatively with the Raman method. Maximum compression residual stress of 1.4 GPa was recorded in the abrasively ground PCD of the smallest grade size while minimum compression residual stress of 0.7 GPa was found in the PCD of the biggest grade. On the contrary, the dominant residual stress in the EDG-eroded PCDs was tensile stress and its magnitude was in the range of 4.7 to 0.4 GPa. Through cutting tests, it was revealed that the residual stress and graphitization influenced the wear mechanism of the tool. It was also observed that abrasive wear dominated the wear pattern of the highly graphitized PCD tools, while breakage through fracture was the main wear mechanism for abrasively ground PCD, which has a structure of lower-level graphitization.